2009
DOI: 10.1097/ftd.0b013e31819743d9
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Mycophenolic Acid and Its Glucuronide Metabolites in Stable Adult Liver Transplant Recipients With Renal Dysfunction on a Low-Dose Calcineurin Inhibitor Regimen and Mycophenolate Mofetil

Abstract: Low-dose calcineurin inhibitors (CNIs) in combination with a fixed dose (2 g/d) of mycophenolate mofetil (MMF) are a strategy to minimize exposure to cyclosporine (CSA) or tacrolimus (TAC) and thus reduce CNI-related side effects. This study compared the pharmacokinetics (PK) of mycophenolic acid (MPA) and its glucuronide metabolites in stable adult liver transplant recipients with moderately impaired renal function converted from a standard to a low-dose CNI regimen in combination with a fixed dose of MMF. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…did not observe any pharmacokinetic differences in free and, total MPA and MPAG. It was probably because of lower blood concentrations of cyclosporine in organ transplant recipients enrolled in their studies (23–25). Patel et al.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…did not observe any pharmacokinetic differences in free and, total MPA and MPAG. It was probably because of lower blood concentrations of cyclosporine in organ transplant recipients enrolled in their studies (23–25). Patel et al.…”
Section: Resultsmentioning
confidence: 99%
“…Beckebaum et al. reported that cyclosporine C 0 ranged from 17 to 35 ng/mL in liver transplant recipients (24). Ting et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…New therapeutic regimens combine immunosuppressants with different intracellular targets to lower blood concentrations and prevent undesired side effects [1-3]. This practice requires a precise and accurate analytical method, especially for the lower ranges of concentrations.…”
Section: Introductionmentioning
confidence: 99%